The relationship of undernutrition/psychosocial factors and developmental outcomes of children in extreme poverty in Ethiopia - Worku, Berhanu Nigussie (BMC Pediatr, 2018)
BACKGROUND: Extreme poverty is severe deprivation of basic needs and services. Children living in extreme poverty may lack adequate parental care and face increased developmental and health risks. However, there is a paucity of literature on the combined influences of undernutrition and psychosocial factors (such as limited play materials, playground, playtime, interactions of children with their peers and mother-child interaction) on children’s developmental outcomes. The main objective of this study was, therefore, to ascertain the association of developmental outcomes and psychosocial factors after controlling nutritional indices. METHODS: A community-based cross-sectional study design was used to compare the developmental outcomes of extremely poor children (N = 819: 420 girls and 399 boys) younger than 5 years versus age-matched reference children (N = 819: 414 girls and 405 boys) in South-West Ethiopia. Using Denver II-Jimma, development in personal-social, language, fine and gross motor skills were assessed, and social-emotional skills were evaluated using the Ages and Stages Questionnaires: Social-Emotional (ASQ: SE). Nutritional status was derived from the anthropometric method. Independent samples t-test was used to detect mean differences in developmental outcomes between extremely poor and reference children. Multiple linear regression analysis was employed to identify nutritional and psychosocial factors associated with the developmental scores of children in extreme poverty. RESULTS: Children in extreme poverty performed worse in all the developmental domains than the reference children. Among the 819 extremely poor children, 325 (39.7%) were stunted, 135 (16.5%) were underweight and 27 (3.3%) were wasted. The results also disclosed that stunting and underweightness were negatively associated with all the developmental skills. After taking into account the effects of stunting and being underweight on the developmental scores, it was observed that limited play activities, limited child-to-child interactions and mother-child relationships were negatively related mainly to gross motor and language performances of children in extreme poverty. CONCLUSION: Undernutrition and psychosocial factors were negatively related to the developmental outcomes, independently, of children living in extreme poverty. Intervention, for these children, should integrate home-based play-assisted developmental stimulation and nutritional rehabilitation.